Fatores de risco associados à distribuição da infecção por Schistosoma mansoni na comunidade do bairro Santa Maria, Aracaju-SE - Santos, Allan Dantas dos (2013)
Schistosomiasis mansoni is a serious parasitic disease, waterborne and chronic disease, which is the etiological agent of Schistosoma mansoni. This is one of the most prevalent parasitic disease in the world. In Sergipe, the disease has expanded from rural to peri-urban areas and the causal factors of this process of expansion and urbanization from this disease have not yet elucidated, thus characterizing a public health problem. This study aimed to determine the association between the risk factors identified in the distribution of infection by S. mansoni in the community of Santa Maria district, municipality of Aracaju-SE. It is a cross-sectional epidemiological study. The survey was conducted in 04 (four) times: a) survey malacological b) parasitological survey census c) a questionnaire to survey the risk factors socioeconomic, behavioral, and environmental contact with the water associated with the occurrence and transmission of disease d) georeferenced analysis of transmission focus disease and human cases of schistosomiasis. In the analysis of descriptive data were used programs BioEstat (version 5.0) and Microsoft Excel 2007. Spatial analysis of the distribution of the infection in the neighborhood led through programs and GPS TrackMaker and terraView 4.1.0 using kernel intensity estimator. Statistical analysis was performed using the chi-square test, G test and multiple logistic regression. It was found that the prevalence of infection was was 5.4% in 2011; prevailed mild infection with 72.7% according to parasite load, in relation to sex of subjects infected, infection with S. mansoni prevalent in males 63.7%. We identified 444 cases of schistosomiasis in the year under study. The eliminations largest egg schistosomiasis were most prevalent adolescents and young adults in the age group 10-39 years. Individuals most at risk for getting sick of schistosomiasis are residing near the springs with their homes accumulating water in the backyard in the winter, unpaved streets, where the individual and the family head have low education, male and age productive (10-59 years), who do not carry water treatment at home and have constant contact with water. In Malacological survey were collected 147 snails of the species Biomphalaria glabrata, being 19.17% rate of infection by S. mansoni in 22 transmitters of disease outbreaks. Spatial analysis of foci of transmission of schistosomiasis indicates the existence of three major clusters in the neighborhood and viewing areas of greatest concentration of cases exposed to different degrees of risk. The survey results allow offering, the municipal health services, a tool that facilitates the understanding of the occurrence and spatial distribution of schistosomiasis.